2013
DOI: 10.1515/joc-2012-0055
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Estimate of Some Propagation Characteristics for the First Higher Order Mode in Graded Index Fiber with Simple Analytic Chebyshev Method

Abstract: Using Chebyshev power series approach, accurate description for the first higher order (LP 11 ) mode of graded index fibers having three different profile shape functions are presented in this paper and applied to predict their propagation characteristics. These characteristics include fractional power guided through the core, excitation efficiency and Petermann I and II spot sizes with their approximate analytic formulations. We have shown that where two and three Chebyshev points in LP 11 mode approximation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“… . We have compared our results with those obtained by Chebyshev method already reported in our earlier paper [15]. It was shown there that the values of propagation characteristics of LP 11 mode in parabolic and triangular index fibers obtained by CPS technique using four Chebyshev points closely matched with standard numerical values.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“… . We have compared our results with those obtained by Chebyshev method already reported in our earlier paper [15]. It was shown there that the values of propagation characteristics of LP 11 mode in parabolic and triangular index fibers obtained by CPS technique using four Chebyshev points closely matched with standard numerical values.…”
Section: Resultssupporting
confidence: 71%
“…Since the current interest is in Two Mode Fibers where LP 01 and LP 11 modes both exist, it is important to find the range within which these modes can exist. We have compared our data with one analytic method like Chebyshev Power Series (CPS) technique, as it is already established as an approximate analytic method for the calculation of different propagation characteristics of graded index fiber in LP 01 and LP 11 mode [14,15]. We found that Chebyshev technique results are in close accordance with our values.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations